Criminal Liability for the Abuse of a New Type of Narcotics (Alpha Propylaminopentiophenone) in Indonesia - Ni Gek Ayu Septi Nohanaa; I Gusti Bagus Suryawan; I Wayan Rideng (Journal Equity of Law and Governance, 2023)
With the rapid development of information technology, the types of Narcotics are increasing, one of which is Alpha Propylaminopenthiophenone, which is a new type of Narcotics that is not yet contained in statutory regulations, so there is a void in norms. Propylaminonepenthiophenone) can be held criminally responsible? 2. What are the arrangements for new types of narcotics users such as Alpha Propylaminonpentionefenone in the future? The use of the method in this study is a type of normative legal research with a statutory regulatory approach, the source of data is through legislation which includes Law Number 35 of 2009 and the purpose of this study is to determine criminal liability for users of a new type of narcotics (alpha propylaminopenthiophenone). in Indonesia. The results of the study can be explained that Alpha Propylamininpenthiophenone has not been regulated in Indonesian Legislation and Users of these substances cannot be held criminally responsible because the Indonesian legal system adheres to the principle of legality, so with regard to this it is necessary to regulate (Alpha Propylaminonpenthiophenone) so that users can be held criminally responsible and should reform the Narcotics Law which states that all substances containing narcotic substances are considered narcotics.